Tendencies of Formation and Development of Modern School Activities in the Context of Modernization of the Education System - Oglu, Taylakov Muhammad Norbek (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is based on the application of new approaches to the effective organization and development of schools, scientific and pedagogical aspects, mechanisms for quality activities. The importance of introducing quality improvement practices based on the innovative cluster of pedagogical education has been identified.